Stunting Prevention and First 1,000 Days of Life Optimisation Programme in Gunungkidul - Andari Wuri Astuti; Siti Fatimah; Lulu Anisa; Resya Aprilia; Cindy Putri Febrianti; Siti Roshaidai Mohd Arifin; Ita Suryani; Mila Savitri (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Stunting is a significant public health issue and the prevalence of stunting in Indonesia was reported at 21.6% in 2022. This study used a mixed-methods approach. The qualitative component employed a single-case embedded study design, data were collected through semi-structured interviews involving 15 participants and analyzed by using a thematic approach using NVivo-12. Meanwhile, the quantitative component utilized a one-group pre-test post-test design involving 155 respondents, data were gathered using questionnaires and were analyzed using paired t-tests with SPSS-26.Participants had a lack of knowledge about stunting. However, they acknowledged various healthy nutrition and health programs for stunting prevention. There were also various programs managed by local government involving multisector bodies, and communities focusing on reducing stunting prevalence. However, there were expectations to strengthen the program strategies by providing home visits, online educational media, adequate facilities, and infrastructure within Integrated Community Services (ICS (Posyandu)). The paired t-test revealed a significant average difference between pre-test and post-test values, with a mean difference of 1.167 and a p-value of <0.008. The ongoing stunting alleviation program demonstrates the government’s commitment to multi-sectoral collaboration and the use of educational media, such as videos, significantly enhances respondents’ knowledge about stunting.